Relationship between chronological age, dental age, and body height using Demirjian method among children aged 4-14 years in Pune - A radiographic study - Rahul J Hegde; Anand Shigli; Pritesh Gawali; Geetanjali Jadhav; Priyanka Garje; Tejas Kulkarni (Wolters Kluwer Medknow Publications, 2020)
Context: The assessment of dental age is useful in the planning of orthodontic treatment, in pediatric dentistry, pediatric endocrinology, and forensic medicine. It is essential for a pediatric dentist to formulate treatment plan and it is a source of complementary information for pediatrician. Changes in the body proportion and composition are the essential elements of growth, especially maturation. Aims: The present study was aimed to correlate the chronological age, dental age, and body height in children from Pune region of Maharashtra, India. Subjects and Methods: Four hundred and thirty-one panoramic radiographs of 177 boys and 254 girls in the age group of 4-14 years were obtained. Chronological age was assessed by recording date of birth. Dental age assessment was done using orthopantamogram following the method described by Demirjian. Body height was recorded using a measuring tape. Results: Chronological age and dental age showed significant positive correlation between male and female sample, i.e., r = 0.905 for males and r = 0.901 for females. Statistically significant correlation was observed between calculated dental age and body height. Conclusions: In the present study, it can be concluded that the Demirjian method of dental age assessment showed high accuracy when applied to pediatric population in Pune.